2007
DOI: 10.1042/cs20070169
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin, sex and hypertension

Abstract: The ETs (endothelins) comprise a family of three 21-amino-acid peptides (ET-1, ET-2 and ET-3) and 31-amino-acid ETs (ET-1(1-31), ET-2(1-31) and ET-3(1-31)). ET-1 is synthesized from a biologically inactive precursor, big ET-1, by ECEs (ET-converting enzymes). The actions of ET-1 are mediated through activation of the G-protein-coupled ET(A) and ET(B) receptors, which are found in a variety of cells in the cardiovascular and renal systems. ET-1 has potent vasoconstrictor, mitogenic, pro-inflammatory and antinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 120 publications
(197 reference statements)
2
52
1
2
Order By: Relevance
“…One possible reason is that MCT potentially has a direct influence on the regulation of COX-2 by E 2 ; another possible reason is that the adjustment mechanisms of E 2 may be cellspecific. It is known that oestrogen modulates both ET-1 gene expression and production [29]. Our data indicate that E 2 not only regulates eNOS and COX-2 expressions, but also reduces ECE levels in MCT-treated rats.…”
Section: Discussionsupporting
confidence: 57%
“…One possible reason is that MCT potentially has a direct influence on the regulation of COX-2 by E 2 ; another possible reason is that the adjustment mechanisms of E 2 may be cellspecific. It is known that oestrogen modulates both ET-1 gene expression and production [29]. Our data indicate that E 2 not only regulates eNOS and COX-2 expressions, but also reduces ECE levels in MCT-treated rats.…”
Section: Discussionsupporting
confidence: 57%
“…It has been reported that ET-1 systems are involved in the sex differences in the incidence of cardiovascular disease, especially hypertension (Tostes et al, 2008). We have also demonstrated that female rats were more resistant to deoxycorticosterone acetate salt-induced hypertension than male rats and this sex difference was abolished by genetic deficiency of the ET B receptor (Kawanishi et al, 2007).…”
Section: Introductionsupporting
confidence: 55%
“…[5][6][7] It has been shown that endogenous vasoactive peptides such as angiotensin II, endothelin-1, urotensin II, and natriuretic peptides play an important role in the regulation of vascular tone in (patho) physiological conditions. [8][9][10][11] Several reports suggested that the signalings of vasoactive peptides, including their production, metabolism, and affected vascular functions, are altered in arteries from hypertensive patients and animal models. 6,10,12) Therefore, the manipulation of vasoactive peptide signaling is one of the most important strategies against the development of vascular dysfunction in hypertension.…”
mentioning
confidence: 99%